High inflations and the Financial System - Leijonhufvud, Axel (Estudios de Economía, 2016)
The economic prospects of Latin America are seen with increasing optimism by the international business community following the economic reforms carried through in a number of countries in recent years. Privatizations and the lowering of trade barriers, including the formation of MercoSur and NAFTA, have received much favorable attention. But most important have been the monetary stabilizations and the fiscal reforms that have made them possible.